Highly efficient ionic‐liquid based solid polymer electrolyte for energy device (RAFM 2022). (February 2023) - Sharma, Harshit; Tomar, Richa; Konwar, Subhrajit; Singh, Pramod K; Chandra Singh, Ram; Kumar, Sushant; Singh, Abhimanyu; Agarwal, Daksh; Yahya, MZA
We have successfully synthesized highly conducting polymer electrolyte incorporated ionic liquid films. There was a rise in conductivity by ionic liquid doping which is clarified by impedance spectroscopy. Fourier transform infra red spectroscopy confirms complexation as well as composite nature. Polarized optical microscopy shows decrease in crysatllinity (more amorphous) by ionic liquid doping. Maximum conducting ionic liquid incorporated polymer electrolyte sandwitched between electrodes, used for fabricating electrical double layer capacitor (EDLC) and dye sensitized solar cell (DSSC) further affirm that these ionic liquid doped polymer electrolyte could be a novel alternative in electrochemical devices.